2021
DOI: 10.1186/s41983-020-00262-4
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of ultrasound-guided multifidus cervicis plane block versus greater occipital nerve block for cervicogenic headache

Abstract: Introduction Traditionally, non-invasive and invasive techniques were used for the treatment of cervicogenic headache (CH). Greater occipital nerve block is the most frequent peripheral nerve block invasive technique used for the management of cervicogenic headache. The purpose of this prospective, double-blinded study was to compare the efficacy of two different techniques: multifidus cervicis plane block and greater occipital nerve block in the treatment of refractory cervicogenic headache by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“… 19 , 24 In total, 196 out of 269 (73%) patients with headaches from the occipital region reported good results after injection with local anesthetics. The reported time of headache relief varied; Bovim and Sand 16 and Mohamed et al 21 reported a mean headache-free period of 30 minutes, and Martínez-Pías et al 20 found a mean headache-free period of 3.5 months. Among the studies that included patients with headache arising from the occipital region, an adverse event rate of 0%–9% was reported, including dizziness, blurring of vision, and hypertension.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 19 , 24 In total, 196 out of 269 (73%) patients with headaches from the occipital region reported good results after injection with local anesthetics. The reported time of headache relief varied; Bovim and Sand 16 and Mohamed et al 21 reported a mean headache-free period of 30 minutes, and Martínez-Pías et al 20 found a mean headache-free period of 3.5 months. Among the studies that included patients with headache arising from the occipital region, an adverse event rate of 0%–9% was reported, including dizziness, blurring of vision, and hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Vincent et al 27 found a VAS improvement of 45.6% after a follow-up of 7 days (Table 2 ). 21 , 25 , 26…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations